Cultivating Nationalism through History Education: A Critical Examination of Pedagogical Practice in Post-Colonial Indonesia - Ummi Indayani; Atno Atno; Bain Bain (Indonesian Journal of History Education, 2026)
Abstract: This study critically examines the cultivation of nationalist values through history education at SMA Negeri 1 Gondang, Indonesia, investigating the disjuncture between policy aspirations and classroom practice in a post-colonial context increasingly shaped by globalisation. Drawing on qualitative case study methodology, the research reveals that while teachers demonstrate commitment to fostering nationalism through the Proclamation of Independence narrative, cultivation remains superficial, characterised by transmission-oriented pedagogy that presents nationalism as an unproblematic value to be absorbed rather than a contested historical construct requiring critical engagement. The absence of explicit learning objectives for nationalism, limited teacher professional development, and the persistence of examination-oriented pedagogies constrain meaningful value cultivation. This study argues that effective nationalist values education in post-colonial contexts requires moving beyond transmission toward critical pedagogy that enables students to interrogate nationalism's historical construction and contemporary relevance.   Abstrak: Studi ini mengkaji penanaman nilai nasionalisme melalui pendidikan sejarah di SMA Negeri 1 Gondang, Indonesia, menyelidiki kesenjangan antara aspirasi kebijakan dan praktik kelas dalam konteks pascakolonial yang dipengaruhi globalisasi. Dengan metodologi studi kasus kualitatif, penelitian mengungkap bahwa meskipun guru berkomitmen menumbuhkan nasionalisme melalui narasi Proklamasi, penanaman tetap dangkal, ditandai pedagogi transmisi yang menyajikan nasionalisme sebagai nilai tak bermasalah untuk diserap, bukan konstruksi historis yang diperdebatkan. Minimnya tujuan eksplisit, terbatasnya pengembangan profesional guru, dan pedagogi berorientasi ujian menghambat penanaman bermakna. Studi berargumen bahwa pendidikan nasionalisme efektif di pascakolonial perlu melampaui transmisi menuju pedagogi kritis yang memungkinkan siswa menginterogasi konstruksi historis dan relevansi kontemporernya.